POST-NONCLASSICAL PHILOSOPHY AND INCLUSION: PLURALITY, COMPLEXITY, AND MULTIVOICEDNESS - Chorieva Madina Alievna (Western European Studies, 2025)
The article explores the philosophical foundations of inclusion within the framework of post-nonclassical philosophy, characterized by plurality, complexity, and multivoicedness. It emphasizes that contemporary society functions as a nonlinear, multilayered system, where traditional models of social interaction are insufficient. The study examines key concepts such as “multiple identities,” “network ontology,” and “dialogicality,” which shape new approaches to integrating diverse social groups. The author concludes that post-nonclassical philosophy provides a methodological basis for understanding inclusion as a principle of equitable coexistence of cultural, social, and individual diversity.
Keywords: post-nonclassical philosophy; inclusion; plurality; complexity